Boundedness of several operators on weighted Herz spaces - Yasuo Komori; Katsuo Matsuoka (Journal of Function Spaces and Applications)
We consider the boundedness of singular integral operators and fractional integral operators on weighted Herz spaces. For this purpose we introduce generalized Herz space. Our results are the best possible.